CLF Based Stabilization of Chaos in PMSM with Uncertain Parameters - Chuansheng Tang; Yuehong Dai; Hua Sun (Institute of Advanced Engineering and Science, 2014)
The robust stabilization problem of chaos suppression for permanent magnet synchronous motors (PMSM) drive system is investigated in presence of parametric uncertainties. Based on control Lyapunov function (CLF) approach, a new state feedback controller is designed to realize the state of the system globally asymptotically stable. The stability of the proposed control scheme is verified via Lyapunov stable theory. Finally, simulation results illustrate the effectiveness of the presented method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4096